TRANSFORMASI DAN EFEK NOMINALISASI BERDASARKAN TEORI CRITICAL LINGUISTIC DALAM WACANA "JUMLAH SAMPAH PESTA TAHUN BARU TURUN" - Via Nugraha; Ratih Sapdiani (Jurnal Semantik, 2020)
The discourse entitled "Jumlah Sampah Pesta Tahun Baru Turun" becomes the center of critical discourse analysis in this study. The formulation of the problem of this research is how to explain critical linguistics, especially language transformation as well as nominalization, and how to analyze the discourse in the discourse "Jumlah Sampah Pesta Tahun Baru Turun " in Kompas media using a critical linguistic scalpel. Based on this formulation, this study aims to explain about Critical Linguistics, especially transformation and nominalization effects, and to describe the results of discourse analysis in the discourse "Jumlah Sampah Pesta Tahun Baru Turun" in Kompas media using a Critical Linguistic scalpel. This study used descriptive qualitative method. The results of the study indicate that the transformation and nominalization effects are thick on the discourse being analyzed. This shows that the use of language in a discourse is able to provide an understanding of different images compared to telling other subjects.